2017
DOI: 10.1523/jneurosci.2628-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized cGMP Responses of Olfactory Sensory Neurons inCaenorhabditis elegans

Abstract: Cyclic guanosine monophosphate (cGMP) plays a crucial role as a second messenger in the regulation of sensory signal transduction in many organisms. In AWC olfactory sensory neurons of , cGMP also has essential and distinctive functions in olfactory sensation and adaptation. According to molecular genetic studies, when nematodes are exposed to odorants, a decrease in cGMP regulates cGMP-gated channels for olfactory sensation. Conversely, for olfactory adaptation, an increase in cGMP activates protein kinase G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
7
23
0
Order By: Relevance
“…These results are consistent with the sensory ending-specific localization of GCYs Nguyen et al, 2014) and the fact that the laser-axotomized AFD sensory ending but not AFD soma changes Ca2+ level in response to temperature stimuli (Clark et al, 2006). Compartmentalized cGMP dynamics are also observed in olfactory sensory neuron AWC (Shidara et al, 2017) and O2-sensing neuron PQR (Couto et al, 2013).…”
Section: Cgmp Level In Afd Dynamically Responds To Temperature Changesupporting
confidence: 83%
“…These results are consistent with the sensory ending-specific localization of GCYs Nguyen et al, 2014) and the fact that the laser-axotomized AFD sensory ending but not AFD soma changes Ca2+ level in response to temperature stimuli (Clark et al, 2006). Compartmentalized cGMP dynamics are also observed in olfactory sensory neuron AWC (Shidara et al, 2017) and O2-sensing neuron PQR (Couto et al, 2013).…”
Section: Cgmp Level In Afd Dynamically Responds To Temperature Changesupporting
confidence: 83%
“…The glutamate input to AIY decreased following odor application and transiently increased following odor removal, in a deterministic manner (Figure 2C). These responses to odor correspond to the responses of sensory neurons (Chalasani et al., 2007, Shidara et al., 2017). Although there were deterministic changes in glutamate input, large Ca 2+ spikes were observed even without odor, and often at the onset of odor stimulation, as reported previously (Chalasani et al., 2007).…”
Section: Resultsmentioning
confidence: 95%
“…, calcium sensors and fluorescent markers for organelles). In the olfactory neuron AWC, this FRET-based sensor showed cilia-compartmentalized cGMP dynamics in response to odorants (Shidara et al 2017). Additionally, Couto et al (2013) found that, in the oxygen-sensing neuron PQR, simultaneous imaging of the cGMP sensor with a calcium sensor in response to a 7–21% increase in oxygen revealed that a decrease in cGMP correlated with an increase in calcium.…”
mentioning
confidence: 99%